The Monopoly on World Cup Broadcasts and Its Impact on Libyan Audience Viewing Patterns: A Field Study (Al-Farooq Journal of Sciences, 2026)
Title: The Monopoly of Broadcasting World Cup Matches and Its Impact on the Viewing Patterns of the Libyan Audience: A Field Study in Tripoli.Prepared by: [Researcher's Name]This field study aimed to investigate the impact of the monopoly and encryption of FIFA World Cup broadcasting rights on the shifting media consumption habits and television viewing patterns of the Libyan audience in the capital, Tripoli. It also explored the technical and spatial coping strategies deployed by the public to bypass these financial barriers. Methodologically, the study utilized a descriptive-analytical approach combined with the audience survey method. A questionnaire, verified for face validity and internal reliability, was administered both electronically and in print to a simple random sample of 400 respondents residing across the municipalities of Greater Tripoli.The researcher reached several key findings, notably a high public passion for permanent and continuous match viewing at a rate of 48.75% despite encryption constraints. The results revealed a forced structural shift in spatial and social viewing patterns; the monopoly eroded stable home-based family viewing rituals, driving a mass migration toward commercial outdoor venues. Attending coffee shops ranked first as a spatial alternative at 37.50%, followed by reliance on local terrestrial wireless re-broadcasting networks at 32.50%, and digital piracy servers (IPTV) at 22.50%. Hypothesis testing confirmed statistically significant differences in alternative preferences based on monthly income and age variables. Economic motivation emerged as the primary driver for bypassing encryption at 46.25%, though these alternatives regularly clashed with the capital's infrastructural challenges, top-lined by electricity blackouts and load shedding at 42.50% and unstable internet speeds at 36.25%. The study recommended empowering the national Libyan television to secure terrestrial broadcasting rights and establishing free public viewing squares by local municipalities to safeguard citizens' rights to entertainment.